Integrated environmental DNA analysis and population assessment revealed a biannual breeding season of the Korean clawed salamander (Onychodactylus koreanus) - Min-Woo Park; Jaejin Park; Jongsun Kim; Jiho Park; Narae Joo; Hahyun Nam; Daesik Park (PLoS ONE, 2026)
Determining the breeding season of a species is key to understanding its life cycle and to ensuring efficient conservation. Determining the breeding season is challenging for subterranean breeders. Environmental DNA (eDNA) applications have been proposed alongside population surveys. In this study, larval influx, adult emergence, and eDNA detection of Onychodactylus koreanus , an external fertilizer, were investigated at underground cave breeding sites every 2 weeks from April 2024 to June 2025 to determine the breeding frequency and season. A major influx of 1-year-old larvae occurred in June and November. Adult emergence occurred in May–June and November–December, but was absent in July–September and February. The timing of major eDNA detection matched the pattern of adult emergence, but did not well reflect the larval influx. Major eDNA detection occurred twice, in April–June and November–December 2024. Three egg clutches were observed on December 23, 2024. On July 28, 2025, 110 eggs were counted at the same spawning site. Our combined results suggest that O. koreanus has two sperate breeding seasons each year, occurring April–June and November–December, and that eDNA detection along with population surveys can be useful to identify the breeding season of subterranean amphibians.